NLRP3 Inflammasome in the Pathophysiology of Hemorrhagic Stroke: A Review - Yujie Luo; Cesar Reis; Sheng Chen (2018)
Hemorrhagic stroke is a devastating disease with high morbidity and mortality. There is still a lack of effective therapeutic approach. The recent studies have shown that the innate immune system plays a significant role in hemorrhagic stroke. Microglia, as major components in innate immune system, are activated and then can release cytokines and chemokines in response to hemorrhagic stroke, and ultimately led to neuroinflammation and brain injury. The NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome is predominantly released by microglia and is believed as the main contributor of neuroinflammation. Several studies have focused on the role of NLRP3 inflammasome in hemorrhagic stroke-induced brain injury, however, the specific mechanism of NLRP3 activation and regulation remains unclear. This review summarized the mechanism of NLRP3 activation and its role in hemorrhagic stroke and discussed the translational significance.